Neurovascular injury in supracondylar fracture of Humerus - Shrestha, KR; Sapkota, R; Rajbhandari, N; Thapa, B; Shrestha, UK (Journal of Institute of Medicine Nepal, 2013)
Introduction: Supracondylar fractures of the humerus are the commonest upper limb fractures in children, accounting for up to 70% of all pediatric elbow fractures. Supracondylar fractures of the humerus can be managed in outpatient setting but are often complicated by neurovascular injury. Methods: Retrospective study including 187 patients who had presented with supracondylar fracture of humerus with 47 neurovascular injuries during the period of July 2007 to June 2011. Out of 142 patients with Gartland type III fracture 107 underwent immediate open reduction, exploration and internal fixation. Results: Vascular injury is commonly associated with type II supracondylar fracture with posterior displacement. Twenty two patients had vascular injury and all of them had satisfactory outcome after surgery. Conclusion: A careful clinical evaluation, urgent surgical treatment and adequate fracture reduction can prevent lifelong handicap. DOI: http://dx.doi.org/10.3126/joim.v34i3.8909 Journal of Institute of Medicine, December, 2012; 34:12-16